Direct Ink Writing of Cement Structures Modified with Nanoscale Additive. Issue 8 (3rd March 2019) - Sajadi, Seyed Mohammad; Boul, Peter J.; Thaemlitz, Carl; Meiyazhagan, Ashok Kumar; Puthirath, Anand B.; Tiwary, Chandra Sekhar; Rahman, Muhammad M.; Ajayan, Pulickel M.
Abstract : Synthetic structures built with cement benefit from high compressive strength, but their brittleness limits their fracture toughness under conditions where repeated, unnegotiable strains are imparted. This could be somewhat alleviated, if complex structures with tunable geometries is created, for example, via direct ink writing (DIW)‐based 3D printing. However, the nature of the slurries used in the DIW printing of cement must be modified with proper rheology to be effectively and programmatically printed with distinct mechanical properties intended for specific applications. Here, the authors have developed a nano‐clay modified cement‐based direct ink that enables high‐resolution 3D printing of complex architected structures of tunable geometries. The developed ink has a significant shear thinning and rapid gel strength properties which facilitate extrusion from a micro‐nozzle (≈400 μm) under ambient conditions conserving the filamentary shape with holding the load of the subsequent printed layer above. A series of architected structures have revealed how nanoscale additive, fabrication process, and architecture of the structures can influence both the stiffness and toughness in the cementitious materials. Understanding these construction principles based on architectures, materials, and processing can change the brittle cement‐based structure to a tough one for structural and functional applications. Abstract : Nanoscale additive modified cement‐based ink enables high‐resolution 3D printing of complex architected structures with tunable geometry, functionality, and mechanical performance.